Nonpharmacologic treatments alone are enough to prevent the neurally mediated syncope: A 3 years follow-up study - Bahar Dehghan; Mohammad Reza Sabri; Marjan Mansourian (International Journal of Preventive Medicine, 2019)
Background: Recurrences are common in neurally mediated syncope. The aim of this study is the evaluation of the effectiveness of nonpharmacologic treatments alone in preventing of syncope relapse. Methods: 70 patients (age 5–20 years) with neurally mediated syncope were enrolled. Thirty patients received pharmacologic therapies along with nonpharmacological methods, and 40 patients received just nonpharmacological treatments then followed them for 36 months. The incidences of different outcomes were analyzed with descriptive statistics using percentages. Results: The recurrence rate of syncope was significantly higher in pharmacological group than in nonpharmacological group in each period of the follow-up (P < 0.001). Conclusions: Nonpharmacologic treatment is very effective in the prevention of syncope relapses and can be a substitute for pharmacologic drugs in the initiation of treatment and if done correctly.